Analisis Pengaruh Penggunaan CDI Racing terhadap Performa Sepeda Motor Matic 115 cc - Aprianto, Wahyu Rizki; Farid, Akhmad; Hermawan, Dadang (Widyagama University of Malang, 2023)
Replacing a standard CDI with a racing CDI is one way to improve ignition in a motorcycle engine and is expected to produce more complete combustion in the combustion chamber. The treatment in this study is the different types of CDIs used on motorcycles. The results show that the effect of CDI replacement on the power produced is a significant difference in power on standard CDI at RPM 5000 which is 5.7 HP while on CDI Rextor at RPM 8000 it is 7.3 HP. The significant difference in torque at RPM 1500 is 18.58 Nm while the CDI Rextor at RPM 2000 is 19.6 Nm. The power and torque produced by CDI Rextor are higher than the standard CDI. The amount of ignition produced by CDI Rextor greatly affects the size of the power and torque produced on the bicycle and the combustion pressure force will be maximized.